2019
DOI: 10.17507/tpls.0906.02
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Conceptual Metaphors to Teaching English Idioms to English-majored Students in Viet Nam

Abstract: The discovery that several figurative idioms are semantically motivated by a common conceptual metaphor (CM) has opened up a path to more systematic and insightful learning. However, it was still unclear to what extent the elaboration of conceptual metaphors (CMs) could facilitate learners’ reception and production of idioms over time. To address this issue, a quasi-experiment was conducted, with the pre-test – post-test design, on a sample of 69 Vietnamese undergraduates. Results revealed that the explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
3
1
Order By: Relevance
“…Guo (2019), with Chinese students, also found positive impact of CMoriented instruction on idioms motivated by structural metaphors rather than orientational and ontological ones. Contrary to most previous findings, Pham and To (2019) concluded that exposition of CMs facilitated Vietnamese students of EFL in reception over an extended period, thus, the approach can be considered more effective than the traditional approach in the long term. Likewise, Pan (2019), exploring idiom instruction by clustering them around the underlying CMs against rote-learning and L1 translation of idioms being presented via functional usage themes, found that in the immediate posttest CM participants were better though not statistically significant, and interestingly acquired better results in the one-week delayed posttest.…”
Section: Introducing Cmt To English Language Classescontrasting
confidence: 95%
See 1 more Smart Citation
“…Guo (2019), with Chinese students, also found positive impact of CMoriented instruction on idioms motivated by structural metaphors rather than orientational and ontological ones. Contrary to most previous findings, Pham and To (2019) concluded that exposition of CMs facilitated Vietnamese students of EFL in reception over an extended period, thus, the approach can be considered more effective than the traditional approach in the long term. Likewise, Pan (2019), exploring idiom instruction by clustering them around the underlying CMs against rote-learning and L1 translation of idioms being presented via functional usage themes, found that in the immediate posttest CM participants were better though not statistically significant, and interestingly acquired better results in the one-week delayed posttest.…”
Section: Introducing Cmt To English Language Classescontrasting
confidence: 95%
“…Since then, a handful of publications have been published to support such initiative in ACL field, particularly in relation to idiom comprehension and retention. The researchers (Kövecses and Szabó, 1996;Boers, 2000;Li, 2003;Beréndi et al, 2008;Kömür and Çimen, 2009;Vasiljevic, 2011;Samani and Hashemian, 2012;Chen and Lai, 2013;Doiz and Elizari, 2013;Hung, 2019;Guo, 2019;Pan, 2019;Pham and To, 2019) are of the opinion that implementing CMs as a medium of teaching idioms with appraising the students how different sets of idioms are motivated by specific CMs aid comprehension and retention of a wide range of idioms.…”
Section: Introducing Cmt To English Language Classesmentioning
confidence: 99%
“…As compared to rote learning, the CMinspired instruction appears to be more demanding in terms of thinking, visualizing, and inferring, but all the efforts turn out to be rewarding as the majority of the students interviewed believed that their knowledge of conceptual metaphors would enhance their retention of the target idioms, especially in the long terms. This finding is in good agreement with Pham and To (2019), which shows that the students who learned idioms with the CM-inspired instruction outperformed their counterparts who were instructed in the traditional method in terms of both reception and production of the target idioms even five weeks after the instruction.…”
Section: Table 4 the Students' Opinions On The Benefits Of The Cm-inspired Instructionsupporting
confidence: 85%
“…Arguments for the adoption of conceptual metaphors include claims that this technique can help the learners enhance their understanding and retention of the target language, explore the link between language and culture and boost their confidence in learning L2 vocabulary in a more insightful way instead of relying on rote memorization Doiz & Elizari, 2013). Several empirical studies have proved that metaphor awareness can help enhance the comprehension, retention, and even production of idiomatic expressions (Khoshniyat & Dowlatabadi, 2014;Kartal & Uner, 2017;Pérez, 2018;Chen, 2019;Pham, 2019;Shan, 2020). In addition, a variety of CM-related activities have been designed and step-by-step guidelines on how to apply conceptual metaphors to teaching idioms have also been proposed to ensure that L2 learners can play an active role in their idiom acquisition with conceptual metaphors as an organizer and motivator of English idiomatic expressions (Pham, 2017;Pham, 2019;Upadhaya & Sudharshana, 2021).…”
Section: Using Conceptual Metaphors To Teach English Idiomsmentioning
confidence: 99%
See 1 more Smart Citation